1998
DOI: 10.1177/156482659801900110
|View full text |Cite
|
Sign up to set email alerts
|

A Lesser-Known Grain, Chenopodium Quinoa: Review of the Chemical Composition of its Edible Parts

Abstract: In this era of ever-increasing world population, newer food and feed crops that have been hitherto neglected are gaining recognition. The rejection of such lesser-known food crops has been due not to any inferiority but to the lack of research resources in the place of origin and often to their being scorned as “poor people's plants.” The genus Chenopodium supplies tasty and nutritious leaves as well as pink- to cream-coloured edible seeds. Tolerance to cold, drought, and salinity and the high lysine content o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0
24

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 40 publications
7
33
0
24
Order By: Relevance
“…This alone shows quinoa to be nutritionally superior to wheat. Another study, by Ahamed et al (1998), had very similar results to these for the chemical composition of quinoa -typical compositions are shown in Table 1. The high protein content of quinoa makes it a great alternative to flour for gluten-free goods.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…This alone shows quinoa to be nutritionally superior to wheat. Another study, by Ahamed et al (1998), had very similar results to these for the chemical composition of quinoa -typical compositions are shown in Table 1. The high protein content of quinoa makes it a great alternative to flour for gluten-free goods.…”
Section: Introductionsupporting
confidence: 66%
“…Abalone et al (2004) indicated that these seeds have 16% to 18% protein, and high lysine and tryptophan content. Ahamed et al (1998) showed amaranth to have 13-18% protein, 6-8% fat, 63% carbohydrates, and 4-14% crude fiber. Similar to quinoa, amaranth has high protein content, making it ideal to use in gluten-free goods.…”
Section: Introductionmentioning
confidence: 99%
“…Con respecto al contenido de saponinas se ha establecido que este predomina en el salvado de la quinoa (2,2% 87 ) siendo la remoción de la cáscara de los granos uno de los procedimientos típicamente usados para reducir el sabor amargo. Se ha estimado que un grado de abrasión de 30% reduce más de un 50% del contenido de saponinas en la quinoa cuyo contenido puede oscilar entre 0,1 y 21% 15,52,95 . En la soja el contenido total puede oscilar entre 0,62 y 6,16% 52,96 .…”
Section: Factores Benéficos Y Adversos Para La Nutriciónunclassified
“…Ahamed et al (1998) mention that quinoa starch has excellent freeze-thaw stability and is resistant to retrogradation. These starches could provide an interesting alternative to replace chemically modified starches.…”
Section: Industrial and Other Potentialmentioning
confidence: 99%